Comparative Study Application Of Extraterritorial Jurisdiction In Competition Law Between Indonesia And Us Antitrust Law: Case Study: Temasek Holdings and VLCC - Meiriska Dewi, Syarah; Anisah, Siti (Scholar Center, 2022)
The USA as a pioneer has published Antitrust Law since the XIX century. Indonesia also has business competition laws which are regulated in Law No. 5 of 1999. However, the scope of the definition of business actors in Indonesia is still very narrow. It does not strictly regulate the extraterritorial principle in Article 1 paragraph 5 so that there are legal loopholes for business actors who are outside the jurisdiction. However, KPPU has already made decisions on business actors domiciled abroad from the case Temasek Holdings, Ltd. (No. 07/KPPU-L/2007) and VLCC (No. 07/KPPU-L/2004). Problem formulation of this research is: how is the definition of a business actor based on Indonesian law and USA law; and how is the application of Extraterritorial Jurisdiction in Indonesia law and USA law? The methodology of this research is normative legal research with library research method by tracing secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. Data were analyzed using qualitative analysis. The results of this study, there are differences in the understanding of business actors in Law No.5 of 1999 and Antitrust Law. Uncertainty regarding foreign elements in Law No.5 of 1999 makes judges use